2011
DOI: 10.1007/s00296-011-2162-x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with treatment of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, progressive, debilitating disease that demands continuous therapy with multiple medications. Noncompliance with disease-modifying drugs may cause disease flares, preventable functional impairment, unnecessary treatment changes, and loss of health care resources. The aim of the current study was to explore self-reported compliance with treatment and the factors contributing to this compliance using a representative sample of an RA patient population in Estonia. Two thousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…It has been repeatedly demonstrated that then immune system plays a pivotal role in the biology of a large array of psychiatric disorders, including not only major depression but also schizophrenia and autism [47][48][49]. Such observations support the possibility that the immune system plays a key pathophysiological role in the concomitant development and progression of psychopathology and autoimmune disorders.…”
Section: Potential Mechanisms Involved In Factors Affecting Response mentioning
confidence: 51%
See 4 more Smart Citations
“…It has been repeatedly demonstrated that then immune system plays a pivotal role in the biology of a large array of psychiatric disorders, including not only major depression but also schizophrenia and autism [47][48][49]. Such observations support the possibility that the immune system plays a key pathophysiological role in the concomitant development and progression of psychopathology and autoimmune disorders.…”
Section: Potential Mechanisms Involved In Factors Affecting Response mentioning
confidence: 51%
“…Communication between physician and patient is crucial to adherence. Muller et al (2012) found that patients who were satisfied with their physicians had significantly higher levels of adherence than those who were not [48]. Other studies have found that improved patient knowledge about the disease and the medication and a higher frequency of visits to the physician are correlated with better adherence [169,170].…”
Section: Patient Education Therapeutic Contract: Promoting Adherencementioning
confidence: 98%
See 3 more Smart Citations